2016
DOI: 10.1186/s12884-016-0854-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards universal access to skilled birth attendance: the process of transforming the role of traditional birth attendants in Rural China

Abstract: BackgroundInstitution-based childbirth, with the ultimate goal of universal access to skilled birth attendance (SBA), has been selected as a key strategy to reduce the maternal mortality rate in many developing countries. However, the question of how to engage traditional birth attendants (TBAs) in the advocacy campaign for SBA poses a number of challenges. This paper aims to demonstrate how TBAs in rural regions of China have been integrated into the health system under a policy of institutional delivery.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 8 publications
0
27
0
1
Order By: Relevance
“…Government support; 3. Clinic support Jiang, et al [ 77 ] 2016 Guangxi province Traditional Birth Attendance (TBAs); Village Maternal Health Care Workers Not reported Mobilization of pregnant women for institutional delivery, assisting with home visit for basic care and escorting pregnant women to the hospital for childbirth. Different levels of training in Maternal Child Health hospitals: emphasized identifying high-risk pregnancies and assisting with referrals; for TBAs, focused on care during childbirth and referral skills; for trained birth attendance (TrBAs), additional midwifery training and were required to conduct at least 30 independent deliveries under the supervision of an obstetrician.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Government support; 3. Clinic support Jiang, et al [ 77 ] 2016 Guangxi province Traditional Birth Attendance (TBAs); Village Maternal Health Care Workers Not reported Mobilization of pregnant women for institutional delivery, assisting with home visit for basic care and escorting pregnant women to the hospital for childbirth. Different levels of training in Maternal Child Health hospitals: emphasized identifying high-risk pregnancies and assisting with referrals; for TBAs, focused on care during childbirth and referral skills; for trained birth attendance (TrBAs), additional midwifery training and were required to conduct at least 30 independent deliveries under the supervision of an obstetrician.…”
Section: Resultsmentioning
confidence: 99%
“…The level of training received by CHWs differed across studies. For example, in a study conducted in Guangxi, the training for TBAs is focused on care during childbirth and referral skills while the training for trained birth attendances (TBAs) included additional midwifery training and conducting of at least 30 independent deliveries under an obstetrician’s supervision [ 77 ]. CHWs also received other types of training including health education communication skills [ 23 ], computer skills [ 79 ], mobile phone app use [ 22 ], TB/HIV control and management [ 40 , 82 ], and verbal autopsy interview skills [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…9 However, it has been reported that the majority of women who delivered at home felt that this option was more comfortable and convenient. 26 28 Therefore, the factors of deliveries at home were not only financial status and transportation, but also comfort and convenience on them. The maternal and child health book was generally distributed to women at health facilities in the Philippines.…”
Section: Discussionmentioning
confidence: 99%
“…Health center based childbirth, with the ultimate achievement of universal access to skilled birth attendance is a key strategy to avert the maternal and newborn rated deaths in many developing countries [19]. It is this same reason as to why projects like the EAMNeCH project focused on mobilization of households for institution delivery and inclusion of delivery at health facility related indicators in the monitoring and evaluation framework.…”
Section: Discussionmentioning
confidence: 99%